Preparation of dual responsive low-molecular-weight hydrogel for long-lasting drug delivery. Issue 22 (1st June 2017) - Tao, Ning; Li, Guotao; Liu, Miaochang; Gao, Wenxia; Wu, Huayue
Abstract: A novel low-molecular-weight hydrogel (LMWG) was fabricated by oligopeptide and phenylboronic acid to obtain a smart molecular hydrogel with dual glucose and pH response for long-term drug delivery in this study. Dual glucose and pH responsiveness of the blank molecular hydrogel was first evaluated by on-line tracking the dynamics curves using UV spectroscopy. Model drugs of phenformin for antidiabetes and doxorubicin for anticancer were selected to evaluate the drug carry and glucose/pH responsive drug release of the molecular hydrogel. The results showed the drug-loaded LMWG had good sustaining and long-lasting drug delivery in physiological or pathological environment. Graphical abstract: